2017
DOI: 10.1371/journal.pone.0170528
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Repetitive Magnetic Stimulation on Single Cortical Pyramidal Neurons

Abstract: Repetitive Transcranial Magnetic Stimulation (rTMS) has been successfully used as a non-invasive therapeutic intervention for several neurological disorders in the clinic as well as an investigative tool for basic neuroscience. rTMS has been shown to induce long-term changes in neuronal circuits in vivo. Such long-term effects of rTMS have been investigated using behavioral, imaging, electrophysiological, and molecular approaches, but there is limited understanding of the immediate effects of TMS on neurons. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 61 publications
6
40
0
Order By: Relevance
“…Such facilitation is thought to involve long-term potentiation (LTP)-like changes in synaptic strength that are widely presumed to be a key cellular mechanism of learning and memory. LTP induced by high-frequency magnetic stimulation (100 Hz) has been directly documented in rat hippocampal slices (Tokay et al, 2009), and related synaptic enhancement has been reported in both other slice preparations and primary cortical cell cultures following 10 and 20 Hz magnetic stimulation (Vlachos et al, 2012;Banerjee et al, 2017). Neuronal activity and LTP regulate the expression of plasticity-related neurotrophins such as brain-derived neurotrophic factor (BDNF), which declines in the AD hippocampus (Phillips et al, 1991), and animal studies confirm that high-frequency rTMS can significantly upregulate BDNF levels (Makowiecki et al, 2014).…”
Section: Potential Mechanisms Of Rtms Benefitsmentioning
confidence: 97%
“…Such facilitation is thought to involve long-term potentiation (LTP)-like changes in synaptic strength that are widely presumed to be a key cellular mechanism of learning and memory. LTP induced by high-frequency magnetic stimulation (100 Hz) has been directly documented in rat hippocampal slices (Tokay et al, 2009), and related synaptic enhancement has been reported in both other slice preparations and primary cortical cell cultures following 10 and 20 Hz magnetic stimulation (Vlachos et al, 2012;Banerjee et al, 2017). Neuronal activity and LTP regulate the expression of plasticity-related neurotrophins such as brain-derived neurotrophic factor (BDNF), which declines in the AD hippocampus (Phillips et al, 1991), and animal studies confirm that high-frequency rTMS can significantly upregulate BDNF levels (Makowiecki et al, 2014).…”
Section: Potential Mechanisms Of Rtms Benefitsmentioning
confidence: 97%
“…Even magnetically induced eddy currents responsible for transcranial magnetic stimulation (TMS) fail to account for the magnetic sensitivity. This is because TMS requires voltage gated ion channels 11 and TRPV4, which was used in the "Magneto2.0" construct, has negligible voltage sensitivity (Fig. S3).…”
mentioning
confidence: 99%
“…This channel gating has been proposed to be mediated by the mechanical force between adjacent nanoparticles, but these forces are at least eight orders of magnitude weaker than the pN-scale forces required to activate mechanoreceptors 14 . Magnetically induced eddy currents responsible for transcranial magnetic stimulation (TMS) also fail to account for the observed magnetic response because TMS requires voltage gated ion channels 17 . The TRPV4 channel, which was used in the "Magneto2.0" construct 12 , has negligible voltage sensitivity ( Fig.…”
mentioning
confidence: 99%
“…For the second experiment, we imaged a new FOV on the same coverslip during stimulation by a magnet or sham magnet. [10][11][12][13][14][15][16][17][18][19][20] FOVs from independent cell cultures were recorded for each condition, yielding R1000 cells per condition. When calculating statistical significance, we considered both individual cells ( Fig.…”
Section: Magnetic Stimulation Of the Channel Magneto20 Under Differementioning
confidence: 99%
“…Although the authors suggested that this response may be mediated by the mechanical force between adjacent nanoparticles, these forces are at least eight orders of magnitude weaker than the pN-scale forces required to activate mechanoreceptors (15). Magnetically induced eddy currents responsible for transcranial magnetic stimulation also fail to account for the observed magnetic response because transcranial magnetic stimulation requires voltage-gated ion channels (19), and the TRPV4 channel used in Magneto2.0 (13) has negligible voltage sensitivity (Fig. S5).…”
Section: Introductionmentioning
confidence: 99%